The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1109/jlt.2002.1018803
|View full text |Cite
|
Sign up to set email alerts
|

Accurate modeling of optical multiplexer/demultiplexer concatenation in transparent multiwavelength optical networks

Abstract: This paper presents an accurate theoretical model for the study of concatenation of optical multiplexers/demultiplexers (MUXs/DMUXs) in transparent multiwavelength optical networks. The model is based on a semianalytical technique for the evaluation of the error probability of the network topology. The error-probability evaluation takes into account arbitrary pulse shapes, arbitrary optical MUX/DMUX, and electronic low-pass filter transfer functions, and non-Gaussian photocurrent statistics at the output of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…These power values are further used for the computation of total power output. In the comparison of model and experimental results, it is observed that Equation (31) is comparable to Equation (11) with n equal to 'l i ', and 'a i ' is equal to '1/m' for computing wavelength dependent output power of wavelength 'λ i ' not equal to 'λ c ', where tolerance limits were taken as 0.5 dBm. For wavelength λ i = λ c , 'a i ' is equal to '1.5/m'.…”
Section: Methodsmentioning
confidence: 99%
“…These power values are further used for the computation of total power output. In the comparison of model and experimental results, it is observed that Equation (31) is comparable to Equation (11) with n equal to 'l i ', and 'a i ' is equal to '1/m' for computing wavelength dependent output power of wavelength 'λ i ' not equal to 'λ c ', where tolerance limits were taken as 0.5 dBm. For wavelength λ i = λ c , 'a i ' is equal to '1.5/m'.…”
Section: Methodsmentioning
confidence: 99%
“…In a TON, signal distortion and noise accumulation, due to optical nodes concatenation, can also impair significantly the TON performance [12,13]. It was shown that it is necessary to choose suitably the filter bandwidth in order to maximize the TON performance when signal distortion and incoherent homodyne crosstalk are present [14].…”
Section: R G Leiria and A V T Cartaxomentioning
confidence: 99%
“…Several works have studied the cascadability of optical MUX/DEMUX and OADM based on AWG [12,15]. However, high channel spacing [15] and an approximated AWG transfer function [12] have been considered.…”
Section: R G Leiria and A V T Cartaxomentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive study of the aforementioned effects are included in the model presented in Ref. [10]. Other extensive studies have been performed for sample WDM optical systems or networks operating at 2.5 Gbps and 10 Gbps that provided a better understanding of the impact of optical filter cascades (amplitude and phase) on the performance and are presented in Refs.…”
Section: Introduction-backgroundmentioning
confidence: 99%